Petrology and Geochemistry of Microgabbro in Watugajah Area, Gedangsari, Southern Mountains - Evi Kurniawati; Nugroho Imam Setiawan; Salahuddin Husein (Jurnal Geologi dan Sumberdaya Mineral, 2023)
An intrusive igneous rock with a columnar joint structure having a height of approximately 55 m cropped out in the Watugajah area, Gedangsari, Gunung Kidul Regency, Yogyakarta Special Province. This region geologically is in the western part of the Southern Mountains, part of the Baturagung Subzone, which belongs to the Kebo Formation. This study aims to characterize the igneous rock in the Watugajah area of the Southern Mountains. It suggests the petrogenetic information of this igneous rock and gives a new consideration of the geological history in the Kebo Formation.Geological field mapping was managed in the research area to identify the correlation with other rock units. Rock samples were collected to characterize their composition by petrographical and geochemical analyses. The results suggest the igneous rocks intruded sedimentary rocks of the Kebo Formation, which consists of intercalations coarse sandstone and tuff, fine sandstone and siltstone, and tuff and fine sandstone units. The igneous rocks are classified as microgabbro and basalt in the form of the sill and dyke intrusions. The microgabbro and basalt consist of plagioclase, clinopyroxene, and magnetite, formed by the cooling of magma in the shallow depths. Based on geochemical studies, the igneous rocks of the Watugajah area were formed by subduction zone tectonic setting with the tholeiitic affinity. Keywords: Gedangsari, microgabbro, Southern Mountains, subduction, Watugajah.